Peningkatan Kemampuan Mengajar Guru dalam Penerapan Project Based Learning melalui Coaching Tatap Muka - Siyam Mardini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The impact of prolonged distance learning causes loss of learning. During Distance Learning the teacher gives a lot of assignments. The results of the Supervisor's academic supervision, the ability to teach teachers is low, so it needs to be improved. The research objective is to improve teachers' teaching skills in applying Project Based Learning through Face-to-Face Coaching in Target Schools. Qualitative research method, data analysis using comparative descriptive analysis, through observation, interviews, documentation, and questionnaires, the subjects were 30 teachers at SD N Kintelan, SD N Timuran, SD N Prawirotaman, and SD Muhammadiyah Danunegaran. Cycle stages: planning, implementing, observing and reflecting. Researchers conducted individual face-to-face coaching to teachers in each school. Face-to-face coaching is carried out for approximately 20 minutes, the teacher explores himself and self-development through giving lots of questions and reinforcement so that there is feedback. Direct face-to-face coaching coaching between researchers and teachers at school. The results of the study after face-to-face coaching, the ability to teach teachers in implementing Project Based Learning has increased. The increase in the teacher's teaching ability was evidenced by the results of the pre-cycle with a low score of 69.56, after the action was taken in cycle 1 the score increased by 13.18 to 82.74 and in cycle 2 it increased by 5.44 with an average score of 88.18. In conclusion, the implementation of Project Based Learning has succeeded in improving the teaching abilities of teachers.